Atypical Hemolytic Uremic Syndrome after Traumatic Rectal Injury: A Case Report - Ji-Hyoun Kang; Donghyun Lee; Yunchul Park (Journal of Trauma and Injury)
Atypical hemolytic uremic syndrome (aHUS) is a rare, progressive, life-threatening condition of thrombotic microangiopathy characterized by thrombocytopenia, microangiopathic hemolytic anemia, and renal impairment. The mechanisms underlying aHUS remain unclear. Herein, we present the first case in the literature of aHUS after a traumatic injury. A 55-year-old male visited the emergency department after a traumatic injury caused by a tree limb. Abdominal computed tomography revealed a rectal wall defect with significant air density in the perirectal space and preperitoneum, implying rectal perforation. Due to the absence of intraperitoneal intestinal perforation, we performed diverting sigmoid loop colostomy. An additional intermittent simple repair was performed due to perianal and anal injuries. One day postoperatively, his urine output abruptly decreased and serum creatinine level increased. His platelet level decreased, and a spiking fever occurred after 2 days. The patient was diagnosed with acute renal failure secondary to aHUS and was treated with fresh frozen plasma replacement. Continuous renal replacement therapy (CRRT) was also started for oliguria and uremic symptoms. The patient received CRRT for 3 days and intermittent hemodialysis thereafter. After hemodialysis and subsequent supportive treatment, his urine output and renal function improved. The hemolytic anemia and thrombocytopenia also gradually improved. Dialysis was terminated on day 22 of admission and the patient was discharged after recovery. This case suggests that that a traumatic event can trigger aHUS, which should be considered in patients who have thrombocytopenia and acute renal failure with microangiopathic hemolytic anemia. Early diagnosis and appropriate management are critical for favorable outcomes.